Cloning, expression, purification, crystallization and X‐ray crystallographic analysis of D‐lactate dehydrogenase from Lactobacillus jensenii. Issue 8 (1st August 2014) - Kim, Sangwoo; Kim, Yong Hwan; Kim, Kyung‐Jin
<x xml:space="preserve">Abstract</x> The thermostable D‐lactate dehydrogenase from Lactobacillus jensenii (LjD‐LDH) is a key enzyme for the production of the D‐form of lactic acid from pyruvate concomitant with the oxidation of NADH to NAD+. The polymers of lactic acid are used as biodegradable bioplastics. The LjD‐LDH protein was crystallized using the hanging‐drop vapour‐diffusion method in the presence of 28%(w/v) polyethylene glycol 400, 100 mM Tris–HCl pH 9, 200 mM magnesium sulfate at 295 K. X‐ray diffraction data were collected to a maximum resolution of 2.1 Å. The crystal belonged to space group P3121, with unit‐cell parameters a = b = 90.5, c = 157.8 Å. With two molecules per asymmetric unit, the crystal volume per unit protein weight (VM) is 2.58 Å3 Da−1, which corresponds to a solvent content of approximately 52.3%. The structure was solved by single‐wavelength anomalous dispersion using a selenomethionine derivative.